A polyurethane air filter element capable of releasing negative oxygen ions and a preparation method thereof
By combining GeO2/Tramen-SiO2 aerogel with the raw materials of the polyurethane air filter element, a polyurethane air filter element that can automatically release negative oxygen ions was prepared, which solved the problem of easy adsorption and saturation of existing air filter elements and low VOCs removal rate, and achieved the effect of long-term and stable release of negative oxygen ions, extending service life and reducing costs.
Patent Information
- Application Number
- CN202411982601.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The air filter element prepared by existing polyurethane foaming materials is mainly purified through physical adsorption, and there are problems such as easy adsorption saturation and low VOCs removal rate. There is no air filter element prepared by polyurethane foaming materials that can directly release negative oxygen ions.
By combining the GeO2/Tramen-SiO2 aerogel with components A and B of the polyurethane air filter element, GeO2/Tramen-SiO2 aerogel was added during the polyurethane foaming process by in-situ modification to prepare a polyurethane air filter element that can automatically release negative oxygen ions.
The long-term stable and slow-release release of negative oxygen ions is achieved, which extends the service life of the air filter element, reduces costs, and does not have a negative impact on the bubble structure of the filter element substrate.
Smart Images

Figure BDA0005221868640000081 
Figure BDA0005221868640000091
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane air filter technology, specifically to a polyurethane air filter that can release negative oxygen ions and its preparation method. Background Technology
[0002] Rigid polyurethane foam (RPUFs) is a type of polyurethane material, referring to polyurethane foam materials with a certain rigidity that do not recover after excessive deformation. Compared with other polymer materials, RPUFs have excellent thermal insulation, waterproofing, sound absorption, shock absorption, adhesion, and chemical stability. They also have high specific strength, good compressibility, and excellent energy absorption and cushioning properties. Due to these advantages, rigid polyurethane foam materials play an irreplaceable role in aerospace equipment, defense weaponry, and energy equipment.
[0003] In modern industry, which pursues high efficiency, environmental protection, and energy conservation, air filters are essential components in various industrial equipment such as automobiles, airplanes, high-speed trains, and air purifiers. Therefore, the selection of materials and optimization of performance are particularly important. Polyester foam, with its unique physical and chemical properties, is gradually becoming a new favorite in the air filter manufacturing field. Polyurethane foam has a dense microporous structure, which can effectively capture and intercept impurities such as dust and grit in the air. Compared with traditional filter materials, polyurethane foam has a higher filtration efficiency.
[0004] Negative oxygen ion concentration, as an important indicator for evaluating air and environmental quality, is receiving increasing attention. Known as "air vitamins" and "longevity factors in the atmosphere," negative oxygen ions have various functions, including eliminating formaldehyde and VOCs, settling dust in the air, inhibiting bacteria, and purifying the air. They can also improve cardiopulmonary function and enhance immunity, making them crucial for environmental quality and human health. Negative oxygen ion functional materials refer to materials that can generate or release negative oxygen ions, and are widely used in air purification, medical treatment, agriculture, water quality management, and food preservation.
[0005] Currently, air filters made of polyurethane foam mainly achieve purification through physical adsorption, which has problems such as easy adsorption saturation and low VOCs removal rate. No air filters made of polyurethane foam that can directly release negative oxygen ions have been reported. Summary of the Invention
[0006] (a) Technical problems to be solved
[0007] To address the shortcomings of existing technologies, this invention provides a polyurethane air filter element that can release negative oxygen ions and its preparation method.
[0008] (II) Technical Solution
[0009] To achieve the above objectives, the present invention provides the following technical solution:
[0010] In a first aspect, the present invention provides a polyurethane air filter element capable of releasing negative oxygen ions, the polyurethane air filter element being made of component A, component B and GeO2 / tourmaline-SiO2 aerogel; wherein component A is composed of the following raw materials: 100-80 parts of polyester polyol, 0-20 parts of polyether polyol, 1-5 parts of crosslinking agent, 1-5 parts of chain extender, 0.1-1 parts of composite catalyst, 0.1-0.5 parts of foaming agent, and 0.1-0.2 parts of foam stabilizer; component B is composed of diphenylmethane diisocyanate (MDI) and polymethylene polyphenyl isocyanate (PAPI) in a mass ratio of 1-2:1.
[0011] Further, in component A, the polyester polyol is one or more of polycaprolactone polyol, phthalic anhydride polyester polyol, and polycarbonate polyol; preferably, the polyester polyol is polycaprolactone polyol and phthalic anhydride polyester polyol in a mass ratio of 1-3:1.
[0012] Further, in component A, the crosslinking agent is one of trimethylolpropane, pentaerythritol, sorbitol, triethanolamine, and diethanolamine; the chain extender is one of 1,3-propanediol, 1,6-hexanediol, neopentyl glycol, 1,4-butanediol, 4,4'-methylenedi(2-chloroaniline), and dimethylthiotoluenediamine; preferably, the crosslinking agent is triethanolamine, and the chain extender is 4,4'-methylenedi(2-chloroaniline).
[0013] Further, in component A, the composite catalyst is at least two of the following: triethylenediamine, dimethylethanolamine, N-ethylmorpholine, di(dodecylsulfonium)dibutyltin, and dibutyltin diacetate; preferably, the composite catalyst is triethylenediamine and dibutyltin diacetate in a mass ratio of 1-2:1.
[0014] Furthermore, in component A, the foaming agent is pentafluoropropane and cyclopentane in a mass ratio of 1:2-3; the foam stabilizer is B8485.
[0015] Further, the GeO2 / tourmaline-SiO2 aerogel is prepared according to the following steps:
[0016] (1) Under stirring conditions, nitric acid, tetraethyl orthosilicate and deionized water in a molar ratio of 2-3:5-8:8-12 are mixed evenly and then stirred at 40-45℃ for more than 24 hours to obtain SiO2 sol for later use.
[0017] (2) Add GeCl4 to anhydrous ethanol and stir for 20-25 min. Then add glacial acetic acid and stir for more than 25 min at 45℃ to form germanium sol for later use. The molar ratio of GeCl4 to glacial acetic acid is 1:1-2.
[0018] (3) Grind tourmaline into nano-sized powder, then mix it evenly with SiO2 sol and germanium sol, and stir at 45°C for more than 40 min. Then add epichlorohydrin and continue stirring for 15 min. Then stop stirring and wait for gelation to obtain GeO2 / tourmaline-SiO2 gel. The mass ratio between tourmaline, SiO2 sol and germanium sol is 0.1-0.2:5-8:0.5-1.
[0019] (4) The GeO2 / tourmaline-SiO2 gel was soaked in anhydrous ethanol at room temperature and aged. The anhydrous ethanol was replaced every 12 hours for more than 3 consecutive times. Then, it was kept at 55°C for 24 hours, filtered, and dried to obtain GeO2 / tourmaline-SiO2 aerogel.
[0020] Secondly, the present invention provides a method for preparing a polyurethane air filter element capable of releasing negative oxygen ions, wherein the air filter element is prepared according to the following steps:
[0021] Add the raw materials of component A into the reactor and mix them evenly. Adjust the material temperature to 25-30℃ and continue stirring. Then, add component B, which is preheated to 25-30℃, and GeO2 / tourmaline-SiO2 aerogel to component A and mix evenly. Pour the mixture into a mold preheated to 40℃, insert the paper filter element into it, and demold after 5-10 minutes to obtain the air filter element.
[0022] Among them, GeO2 / tourmaline-SiO2 aerogel accounts for 1-5% of the total mass of components A and B.
[0023] (III) Beneficial Effects
[0024] The polyurethane air filter element that releases negative oxygen ions provided by this invention is prepared by preparing a GeO2 / tourmaline functional material that releases negative oxygen ions into a GeO2 / tourmaline-SiO2 aerogel, and then adding it during the polyurethane foaming process through in-situ modification. The air filter element provided by this invention can achieve autonomous release of negative oxygen ions and can stably and slowly release negative oxygen ions over a long period of time.
[0025] The preparation method provided by this invention enables the functional material GeO2 / tourmaline that can release negative oxygen ions to be uniformly dispersed in the pores of the filter element substrate without negatively affecting the pore structure of the filter element substrate. This ensures the original filtration capacity of the filter element substrate while providing favorable conditions for the release of negative oxygen ions.
[0026] Furthermore, the present invention provides a GeO2 / tourmaline-SiO2 aerogel that can significantly improve the stability of the functional material GeO2 / tourmaline that can release negative oxygen ions. Moreover, the GeO2 / tourmaline-SiO2 aerogel is added in situ during the polyurethane foaming process, which can make GeO2 / tourmaline exist stably in the pores of the filter element substrate, avoiding the loss of negative oxygen ion functional components during repeated use. The air filter element prepared by the present invention can still maintain a high negative oxygen ion release capacity after being repeatedly washed with water 5 times after 90 days, thus extending the service life of the negative oxygen ion air filter element and reducing costs. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Example 1
[0029] GeO2 / tourmaline-SiO2 aerogel was prepared according to the following steps:
[0030] (1) Under stirring conditions, nitric acid, tetraethyl orthosilicate and deionized water in a molar ratio of 3:8:10 were mixed evenly and then stirred at 45°C for more than 24 hours to obtain SiO2 sol for later use.
[0031] (2) Add GeCl4 to anhydrous ethanol and stir for 25 min. Then add glacial acetic acid and stir for more than 25 min at 45°C to form germanium sol for later use. The molar ratio of GeCl4 to glacial acetic acid is 1:1.8.
[0032] (3) Grind tourmaline into nano-sized powder, then mix it evenly with SiO2 sol and germanium sol, and stir at 45°C for more than 40 min. Then add epichlorohydrin and continue stirring for 15 min. Then stop stirring and wait for gelation to obtain GeO2 / tourmaline-SiO2 gel. The mass ratio between tourmaline, SiO2 sol and germanium sol is 0.1:5:1.
[0033] (4) The GeO2 / tourmaline-SiO2 gel was soaked in anhydrous ethanol at room temperature and aged. The anhydrous ethanol was replaced every 12 hours for more than 3 consecutive times. Then, it was kept at 55°C for 24 hours, filtered, and dried to obtain GeO2 / tourmaline-SiO2 aerogel.
[0034] Example 2
[0035] A polyurethane air filter element capable of releasing negative oxygen ions, the polyurethane air filter element being made of component A, component B, and GeO2 / tourmaline-SiO2 aerogel; wherein component A is composed of the following raw materials: 80 parts polyester polyol, 10 parts polyether polyol, 3 parts crosslinking agent, 2 parts chain extender, 0.5 parts composite catalyst, 0.2 parts foaming agent, and 0.1 parts foam stabilizer; component B is composed of diphenylmethane diisocyanate (MDI) and polymethylene polyphenyl isocyanate (PAPI) in a mass ratio of 1-2:1.
[0036] In component A, the polyester polyol is a mixture of polycaprolactone polyol and phthalic anhydride polyester polyol in a mass ratio of 3:1; the molecular weights of the polycaprolactone polyol and phthalic anhydride polyester polyol are 5000 and 7000, respectively; the molecular weight of the polyether polyol is 5000; the crosslinking agent is triethanolamine; the chain extender is 4,4'-methylenebis(2-chloroaniline); the composite catalyst is a mixture of triethylenediamine and dibutyltin diacetate in a mass ratio of 1:1; the foaming agent is a mixture of pentafluoropropane and cyclopentane in a mass ratio of 1:2.5; and the foam stabilizer is B8485. The GeO2 / tourmaline-SiO2 aerogel was prepared as described in Example 1.
[0037] The air filter element is prepared according to the following steps:
[0038] Add the raw materials of component A into the reactor and mix them evenly. Adjust the material temperature to 25-30℃ and continue stirring. Then, add component B, which is preheated to 25-30℃, and GeO2 / tourmaline-SiO2 aerogel to component A and mix evenly. Pour the mixture into a mold preheated to 40℃, insert the paper filter element into it, and demold after 5-10 minutes to obtain the air filter element.
[0039] Among them, GeO2 / tourmaline-SiO2 aerogel accounts for 3% of the total mass of components A and B.
[0040] Example 3
[0041] The difference between this embodiment and Embodiment 2 is as follows:
[0042] The polyurethane air filter is made of component A, component B, and GeO2 / tourmaline-SiO2 aerogel; wherein component A is composed of the following raw materials: 80 parts polyester polyol, 10 parts polyether polyol, 3 parts crosslinking agent, 2 parts chain extender, 0.5 parts composite catalyst, 0.2 parts foaming agent, and 0.1 parts foam stabilizer; component B is composed of diphenylmethane diisocyanate (MDI) and polymethylene polyphenyl isocyanate (PAPI) in a mass ratio of 1-2:1.
[0043] In component A, the polyester polyol is polycaprolactone polyol with a molecular weight of 5000; the crosslinking agent is diethanolamine; the chain extender is 1,4-butanediol; the composite catalyst is triethylenediamine and dibutyltin diacetate in a mass ratio of 2:1; and the foaming agent is pentafluoropropane and cyclopentane in a mass ratio of 1:2.
[0044] GeO2 / tourmaline-SiO2 aerogel accounts for 3% of the total mass of components A and B.
[0045] Example 4
[0046] The difference between this embodiment and embodiment 2 is that...
[0047] The polyurethane air filter is made of component A, component B, and GeO2 / tourmaline-SiO2 aerogel; component A is composed of the following raw materials: 85 parts polyester polyol, 5 parts polyether polyol, 2.5 parts crosslinking agent, 1.5 parts chain extender, 0.3 parts composite catalyst, 0.25 parts foaming agent, and 0.15 parts foam stabilizer; component B is composed of diphenylmethane diisocyanate (MDI) and polymethylene polyphenyl isocyanate (PAPI) in a mass ratio of 2:1.
[0048] In component A, the polyester polyol is composed of polycaprolactone polyol (molecular weight 5000) and polycarbonate polyol (molecular weight 6000) in a mass ratio of 3:1; the crosslinking agent is trimethylolpropane; the chain extender is 1,4,4'-methylenebis(2-chloroaniline); and the composite catalyst is triethylenediamine and dibutyltin diacetate in a mass ratio of 1.5:1.
[0049] GeO2 / tourmaline-SiO2 aerogel accounts for 3% of the total mass of components A and B.
[0050] Example 5
[0051] In a first aspect, the present invention provides a polyurethane air filter element capable of releasing negative oxygen ions, the polyurethane air filter element being made of component A, component B and GeO2 / tourmaline-SiO2 aerogel; wherein component A is composed of the following raw materials: 90 parts polyester polyol, 8 parts polyether polyol, 3 parts crosslinking agent, 2.5 parts chain extender, 0.6 parts composite catalyst, 0.2 parts foaming agent, and 0.16 parts foam stabilizer; component B is composed of diphenylmethane diisocyanate (MDI) and polymethylene polyphenyl isocyanate (PAPI) in a mass ratio of 1.5:1.
[0052] Furthermore, in component A, the polyester polyol is a mixture of polycaprolactone polyol and phthalic anhydride polyester polyol in a mass ratio of 3:1; the crosslinking agent is triethanolamine; the chain extender is 4,4'-methylenebis(2-chloroaniline); and the composite catalyst is a mixture of triethylenediamine and dibutyltin diacetate in a mass ratio of 1-2:1.
[0053] GeO2 / tourmaline-SiO2 aerogel accounts for 3% of the total mass of components A and B.
[0054] Comparative Example 1
[0055] An air filter element is prepared according to the following steps:
[0056] Add the raw materials of component A into the reactor and mix them evenly. Adjust the material temperature to 25-30℃ and continue stirring. Then add component B, which is preheated to 25-30℃, into component A and mix evenly. Pour the mixture into a mold preheated to 40℃, insert the paper filter element into it, and demold after 5-10 minutes to obtain the filter element substrate.
[0057] The composition of components A and B is consistent with that of Example 2.
[0058] Comparative Example 2
[0059] An air filter element is prepared according to the following steps:
[0060] (1) Add the raw materials of component A into the reactor and mix them evenly. Adjust the material temperature to 25-30℃ and continue stirring. Then add component B, which is preheated to 25-30℃, into component A and mix evenly. Pour the mixture into a mold preheated to 40℃, insert the paper filter element into it, and demold after 5-10 minutes to obtain the filter element substrate.
[0061] (2) The nano-sized tourmaline powder is uniformly mixed with GeO2 and dispersed in an aqueous emulsion to obtain a negative oxygen ion spray liquid;
[0062] (3) The negative oxygen ion spray liquid obtained in step (2) is uniformly sprayed onto the surface of the filter element substrate by high pressure spraying, and then cured and dried at 75°C to obtain the air filter element.
[0063] The composition of components A and B is consistent with that of Example 2.
[0064] The content of tourmaline and Ge remains consistent with that in Example 2.
[0065] Comparative Example 3
[0066] An air filter element is prepared according to the following steps:
[0067] (1) Nano-sized tourmaline powder and GeO2 were uniformly dispersed in anhydrous ethanol to obtain a negative oxygen ion dispersion for later use.
[0068] (2) Add each raw material of component A to the reactor and mix evenly. Adjust the material temperature to 25-30℃ and continue stirring. Then add component B, which is preheated to 25-30℃, and negative oxygen ion dispersion to component A and mix evenly. Pour the mixture into a mold preheated to 40℃, insert the paper filter element into it, and demold after 5-10 minutes to obtain the air filter element.
[0069] The composition of components A and B is consistent with that of Example 2.
[0070] The content of tourmaline and Ge remains consistent with that in Example 2.
[0071] Comparative Example 4
[0072] An air filter element is prepared according to the following steps:
[0073] (1) Add the raw materials of component A into the reactor and mix them evenly. Adjust the material temperature to 25-30℃ and continue stirring. Then add component B, which is preheated to 25-30℃, into component A and mix evenly. Pour the mixture into a mold preheated to 40℃, insert the paper filter element into it, and demold after 5-10 minutes to obtain the filter element substrate.
[0074] (2) Disperse GeO2 / tourmaline-SiO2 aerogel into an aqueous emulsion to obtain a negative oxygen ion spraying liquid;
[0075] (3) The negative oxygen ion spray liquid obtained in step (2) is uniformly sprayed onto the surface of the filter element substrate by high pressure spraying, and then cured and dried at 75°C to obtain the air filter element.
[0076] The composition of components A and B is consistent with that of Example 2.
[0077] GeO2 / tourmaline-SiO2 aerogel was prepared according to the method described in Example 1; the content of tourmaline and Ge was kept consistent with that in Example 2.
[0078] Experimental Example 1
[0079] The effect of negative oxygen ion functional modification on the pore structure of polyurethane air filter elements
[0080] Test method: The morphology of polyurethane air filter cells was observed using an SMZ-1500 stereo microscope at 10x and 20x magnification. The pore size, pore shape coefficient, and pore wall thickness were recorded.
[0081] Test samples: Samples prepared in Examples 2-5, Comparative Examples 1 and 3
[0082] Test results: The pore structure results of each sample are shown in Table 1. The pore structure of the air filter elements prepared in Examples 2-5 is basically consistent with that of Comparative Example 1, indicating that GeO2 / tourmaline-SiO2 aerogel has no effect on the formation of pores during the polyurethane foaming process. Compared with Comparative Example 3, the direct addition of tourmaline and GeO2 during the polyurethane foaming process in Example 2 will cause uneven foaming, collapse, increased pore size, pore shape variation, and thickened pore walls due to uneven dispersion, which will have adverse effects on the filtration performance of the filter material.
[0083] Table 1 shows the pore structures of the samples prepared in Examples 2-5, Comparative Examples 1 and 3.
[0084]
[0085] Experimental Example 2
[0086] Negative oxygen ion release capacity test
[0087] Test method: The space for testing the negative ion release of the material is V = 1m. 3 The sealed wooden box contains a 1m³ negative ion air filter material. 2 Lay the filter media flat so that its contact area S = 1m² 2 The test lasted 90 days under normal temperature and pressure, and 60% humidity conditions. The ion counter used was an AN-500 type air-start negative ion detector, purchased from Chongqing Anen Environmental Technology Co., Ltd., with a resolution of 1 ion / cm². 3 The measurement accuracy for negative oxygen ions is ±15%. The negative ion concentration test method follows JC / T 2110-2012 "Indoor Air Ion Concentration Test Method". The negative oxygen ion concentrations were recorded at 1 day, 90 days, and after 90 days, the negative oxygen ion concentration of the filter material sample was recorded after repeated washing and drying five times.
[0088] Test materials: Air filter materials prepared in Example 2 and Comparative Examples 2-4.
[0089] The test results are shown in Table 1. The air filter material prepared in Example 2 released the largest number of negative oxygen ions, and the concentration of negative oxygen ions in the wooden box remained stable during the 90-day experimental period, with a slight increasing trend. After being washed five times with water after 90 days, the air filter material prepared in Example 2 still maintained a high capacity for releasing negative oxygen ions.
[0090] Comparative Example 3 involved directly adding tourmaline and GeO2 during the polyurethane foaming process. As demonstrated in Experiment 1, this preparation method leads to the collapse of the cell structure in the filter substrate, resulting in excessively large pore sizes and thick pore walls. Furthermore, the tourmaline and GeO2 exhibit uneven dispersion, which further results in a significantly lower negative oxygen ion release rate compared to the air filter prepared in Example 2.
[0091] Comparative Examples 2 and 4 both used a spray coating method to cover tourmaline and GeO2 onto the surface of the filter substrate. Compared with Example 2, on day 1 of the experiment, the concentration of negative oxygen ions released by the three filter elements was all above 3200 (S·cm). 3 Above this, on day 90 of the experiment, the concentration of negative oxygen ions released by the filter cartridge of Comparative Example 2 decreased to 2800 (S·cm). 3 The concentration of negative oxygen ions released by the filter cartridges of Comparative Example 4 and Example 2 can still be maintained at 3200 ions (S·cm). 3 The results indicate that preparing tourmaline and GeO2 into an aerogel can significantly enhance the ability of air filter materials to release negative oxygen ions.
[0092] Compared with Example 2, after 90 days and five repeated water washings of the filter element, the concentration of negative oxygen ions released by the filter element of Comparative Example 4 decreased significantly, while the concentration of negative oxygen ions released by the filter element of Example 2 remained at 3700 ions (S·cm). 3 The results indicate that after repeated washing, the GeO2 / tourmaline-SiO2 aerogel applied to the filter substrate surface by spraying will cause peeling and loss, and the modification of negative oxygen ions is unstable, resulting in a decrease in the air filter's ability to release negative oxygen ions. This invention adds GeO2 / tourmaline-SiO2 aerogel in situ during the polyurethane foaming process. This method not only does not affect the filter's pore structure but also ensures that GeO2 / tourmaline is uniformly dispersed in the pores, improves the stability of negative oxygen ion release from GeO2 / tourmaline, extends the service life of the air filter material, and reduces costs.
[0093] Table 2. Test results of negative oxygen ion release capacity
[0094]
[0095] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A polyurethane air filter element capable of releasing negative oxygen ions, characterized in that: The polyurethane air filter element is made of component A, component B and GeO2 / tourmaline-SiO2 aerogel; wherein component A is composed of the following raw materials: 100-80 parts of polyester polyol, 0-20 parts of polyether polyol, 1-5 parts of crosslinking agent, 1-5 parts of chain extender, 0.1-1 parts of composite catalyst, 0.1-0.5 parts of foaming agent and 0.1-0.2 parts of foam stabilizer; component B is composed of diphenylmethane diisocyanate (MDI) and polymethylene polyphenyl isocyanate (PAPI) in a mass ratio of 1-2:
1.
2. A polyurethane air filter element capable of releasing negative oxygen ions as claimed in claim 1, characterized in that: The polyester polyol is one or more of polycaprolactone polyol, phthalic anhydride polyester polyol and polycarbonate polyol.
3. A polyurethane air filter element capable of releasing negative oxygen ions as claimed in claim 1, characterized in that: The cross-linking agent is one of trimethylolpropane, pentaerythritol, sorbitol, triethanolamine, and diethanolamine; the chain extender is one of 1,3-propylene glycol, 1,6-hexanediol, neopentyl glycol, 1,4-butanediol, 4,4'-methylenebis(2-chloroaniline), and dimethylthiotoluenediamine; the composite catalyst is at least two of triethylenediamine, dimethylethanolamine, N-ethylmorpholine, di(dodecylsulfide)dibutyltin, and dibutyltin diacetate; preferably, the composite catalyst is triethylenediamine and dibutyltin diacetate in a mass ratio of 1-2:1; the foaming agent is pentafluoropropane and cyclopentane in a mass ratio of 1:2-3; and the foam stabilizer is B8485.
4. A polyurethane air filter element capable of releasing negative oxygen ions as claimed in claim 1, characterized in that: The GeO2 / tourmaline-SiO2 aerogel is prepared according to the following steps: (1) Under stirring conditions, nitric acid, ethyl orthosilicate and deionized water in a molar ratio of 2-3:5-8:8-12 are mixed uniformly, and then stirred at 40-45° C. for more than 24 hours to obtain SiO2 sol for standby use; (2) adding GeCl4 to anhydrous ethanol, stirring for 20-25 minutes, then adding glacial acetic acid and stirring at 45° C. for more than 25 minutes to form a germanium sol for later use; wherein the molar ratio of GeCl4 to glacial acetic acid is 1:1-2; (3) Grinding tourmaline into nanometer-scale powder, then mixing it evenly with SiO2 sol and germanium sol, and stirring it at 45°C for more than 40 minutes, then adding epichlorohydrin and continuing stirring for 15 minutes, then stopping stirring and waiting for gelation to obtain GeO2 / tourmaline-SiO2 gel; (4) Soaking the GeO2 / tourmaline-SiO2 gel in anhydrous ethanol at room temperature for aging, during which the anhydrous ethanol is replaced every 12 hours for more than 3 times, then keeping it warm at 55°C for 24 hours, filtering, and drying to obtain GeO2 / tourmaline-SiO2 aerogel.
5. A polyurethane air filter element capable of releasing negative oxygen ions as claimed in claim 4, characterized in that: In the step (3) of preparing GeO2 / tourmaline-SiO2 aerogel, the mass ratio of tourmaline, SiO2 sol and germanium sol is 0.1-0.2:5-8:0.5-1.
6. The method for preparing a polyurethane air filter element capable of releasing negative oxygen ions as claimed in claim 1, characterized in that: The air filter element is prepared according to the following steps: Add the raw materials of component A into the reactor and mix them evenly. Adjust the material temperature to 25-30°C and continue stirring. Then add component B and GeO2 / tourmaline-SiO2 aerogel preheated to 25-30°C into component A and mix them evenly. Pour the mixture into a mold preheated to 40°C, insert the paper filter element into it, and demold after 5-10 minutes to obtain the air filter element.
7. The method for preparing a polyurethane air filter element capable of releasing negative oxygen ions as claimed in claim 6, characterized in that: The GeO2 / tourmaline-SiO2 aerogel accounts for 1-5% of the total mass of the A component and the B component.